Analisis Indeks Kepuasan Masyarakat Terhadap Pelayanan Publik Pada BP2T Kota Tanjungpinang - Ely Kartikaningdyah (JURNAL INTEGRASI, 2012)
Public service is carried out by government officials in various service sectors related to meeting the needs of civil rights and basic needs are felt not in accordance with the demands and expectations of society. This can be known among others from the number of complaints, the complaints submitted by the public through the media or directly to the service unit, both related to systems and procedures are still cumbersome, not transparent, less informative, less accommodating and less consistent so it does not guarantee certainty (legal, time and cost) as well as the persistence of the practice of unauthorized charges. It needs to do an assessment of public service to the public using the service. This research uses descriptive quantitative research with a sample of 150 respondents respondents were users of public services in Integrated Permitting Services Agency (BP2T) Tanjungpinang. The purpose of this study to determine how the index of people's satisfaction with public services to the users of the service. Data analysis techniques using the Community Satisfaction Index (HPI) is calculated using the weighted average value of each element of the service by making MenPan Number 63/KEP / M.PAN/7/2003 results showed that overall satisfaction index of the community will Tanjungpinang BP2T service can be said in good condition, and still must be improved because there are some indicators that show the performance indices are not good. Of the 14 indicators studied there were 12 indicators in the category of good service (service procedures, conditions of service, clarity of service officers, discipline officers, officer liability, the ability of service personnel, ministry of justice obtain, politeness and friendliness of staff, the reasonableness of service charges, the charge service and environmental comfort and safety of the environment and capable of satisfactory use of services) while the two other indicators are not included in either category (speed and certainty attendant service schedule).